Stodolní ulice à Ostrava : un exemple de régénération du centre d’une ville post-socialiste en République tchèque - Ondřej Slach; Tomáš Boruta; Pavel Bednář; Jaroslav Koutský (Territoire en Mouvement)
The following contribution deals with regeneration process in a part of the Ostrava city centre and specifically with establishment of a cultural city district in conditions of a post-socialistic city with strong industrial tradition. The aim of the contribution is to analyze the cultural city district establishment and to discuss its gradual transformation into a consumption or entertainment city area. The basic theoretical frame is based on concepts characteristic for post-industrial cities in developed states which are modified for the needs of research in post-socialistic city conditions. Increased emphasis is devoted to the significance and the role of artists in the entertainment area regeneration as well as to the overall development of the whole area of Stodolní street up till now. At the end of the contribution present results of the regeneration process are discussed, moreover there are mentioned some possibilities and presumptions of this area further development.